Analisis kelayakan pengolahan ikan tuna pada usaha kelompok produksi olahan hasil perikanan (studi kasus abon ikan tuna ingkita di Desa Sampuabalo Kecamatan Siotapina Kabupaten Buton) - Rahmayani, Wa Ode Elsy; Yusuf, Sarini; Effendy, Wa Ode Nilda A.; Sidiq, Azwar (Universitas Halu Oleo, 2024)
This study aimed to determine the feasibility analysis of tuna fish processing in the Processed Fishery Products Production Group Business (Case Study of Ingkita Tuna Fish Shreds in Sampuabalo Village, Siotapina District, Buton Regency) Southeast Sulawesi. The types of research data were quantitative data and qualitative data. Data sources came from primary data and secondary data that obtained through interviews, observation, recording and literature study. Data was analyzed using financial analysis consisting of cost, revenue, income and business feasibility analysis. The results showed that fixed costs consist of equipment depreciation costs of IDR 115,554, additional costs of IDR 4,571,333, so that the total fixed costs were IDR 4,571,333. Variable costs consisted of raw material costs and additional costs. Raw material costs were IDR 5,400,000, and additional costs of IDR 6,036,000, so that the total variable costs were IDR 11,436,000. The total production costs incurred by the Ingkita tuna floss entrepreneur were IDR 16,122,887. The month- long income of the Ingkita tuna floss entrepreneur was IDR 27,000,000, with a month's income of IDR 10,877,113 and income/production of IDR 1,812,852. R/C ratio analysis showed a value of 1.67, It’s meaning that the business had profitable prospects if developed.